Effect of HSP27 and Cofilin in the injury of hypoxia/reoxygenation on hepatocyte membrane F-actin microfilaments. Issue 16 (April 2017) - Zhang, Yafei; Wang, Jiazhong; Ji, Hong; Lu, Hongwei; Lu, Le; Wang, Jinlong; Li, Yiming
Abstract : Abstract: Hypoxia–reoxygenation (H/R) injury hepatocyte models were established to simulate the ischemia/reperfusion injury of transplanted organ. Through the study of the molecular mechanism of H/R on the F-actin damage of the liver cytomembrane, the mechanism of F-actin damage induced by ischemia and reperfusion was studied from the level of cell and molecule. The hypoxic environment of cells in vitro was simulated by chemical hypoxia agent CoCl2 . Liver cells were detected by MTT, H/R group was subdivided into 3 subgroups: H/R 2, 4, and 6 h. Changes of cell shape and the growth state, apoptosis, ultrastructural changes, and the changes in F-actin microfilament content were observed. Heat shock protein 27 (HSP27), Cofilin, and F-actin gene and protein levels were determined by real-time polymerase chain reaction and western blot assay, respectively. Cells showed circular adherence growth under normal circumstances, while the spindle cells and shedding cells were significantly increased in H/R groups. Apoptosis cells in H/R group were increased significantly with the extension of hypoxia time. The number of endoplasmic reticulum was decreased significantly in the H/R group, the mitochondrion hydropic was degenerated and the glycogen was disappeared. The F-actin fibers in the H/R group were disordered, the morphology of the fibers was obviously decreased, and the fluorescence staining decreased obviously ( P  < .05). The transcription and expression levels of HSP27, Cofilin, and F-actin were significantly lower than those in the control group ( P  < .05). These results demonstrate that H/R can affect the correct assembly of F-actin microfilaments and weakens the normal cycle of F-actin microfilaments through inhibiting the protein expression and gene transcription of HSP27 and Cofilin in hepatocytes, thereby changing the skeleton of F-actin microfilaments.